2020
DOI: 10.2174/1566524019666191129104153
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effect of Fresh Pomegranate Juice on Serum Cortisol and Thyroxine in Patients with type 2 Diabetes

Abstract: Background: The effect of pomegranate juice on type 2 diabetic conditions has been determined in various occasions. However, such an effect on cortisol and thyroxine hormones, which are major controllers of energy metabolism, is not yet revealed. Objectives: this study, we intended to measure the short-term effect of fresh pomegranate juice on serum cortisol and thyroxine in patients with type 2 diabetes. Materials and Methods: This study was a randomized clinical trial in which 89 fasted patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Collectively, this evidence confirms the ACE inhibition activity and consequently the hypotensive response of pomegranate juice in the human body. Alternatively, in our recent published clinical trial, we have shown that the observed antihypertensive effect of fresh pomegranate juice in humans may be modulated by a reduction in the cortisol level [ 34 ].…”
Section: Possible Beneficial Effects Of Pomegranate Juice In Covid-19...mentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, this evidence confirms the ACE inhibition activity and consequently the hypotensive response of pomegranate juice in the human body. Alternatively, in our recent published clinical trial, we have shown that the observed antihypertensive effect of fresh pomegranate juice in humans may be modulated by a reduction in the cortisol level [ 34 ].…”
Section: Possible Beneficial Effects Of Pomegranate Juice In Covid-19...mentioning
confidence: 99%
“…Mechanistically, pomegranate juice may exert its antihyperglycemic response via enhancing β -cell function, reducing insulin resistance, decreasing cortisol level [ 34 ], and minimizing oxidative stress state [ 24 ], which is an imbalance between oxidants (e.g., reactive oxygen species) and antioxidants [ 51 , 52 ]. The later mechanistic route may be attributable to enhancing activity of vital antioxidant enzymes such as catalase, superoxide dismutase, and glutathione reductase [ 53 ], direct neutralization of free radicals such as hydroxyl radical or superoxide ion, decreasing synthesis of resistin [ 54 ], which is a hormone secreted from adipose tissue and found to be associated with type 2 diabetes [ 55 ], increasing metal binding activity [ 56 ], and activating or inhibiting transcriptional factors such as peroxisome proliferator-activated receptor gamma (PPAR- γ ) and/or nuclear factor- κ B (NF- κ B) [ 24 , 57 , 58 ].…”
Section: Possible Beneficial Effects Of Pomegranate Juice In Covid-19...mentioning
confidence: 99%
“…Intake of fresh PJ (1.5 mL/kg) on 89 T2D patients showed remarkable lower levels of serum cortisol one hour after consumption ( p < 0.0001) which was not related to FBG level or gender [ 103 ].…”
Section: Clinical Studies On Different Diseasesmentioning
confidence: 99%